Modern and neogene analogues for productive subsurface carbonate systems in SE Asia - Madden, Robert Henry Christopher (Curtin University, 2013)
This combined sedimentological, diagenetic and remote sensing study of SE Asian Cenozoic carbonate systems has implications for the understanding of how depositional and diagenetic conditions unique to the equatorial tropics influence regional hydrocarbon reservoir development. Most modern analogues used to help evaluate carbonate development and their subsurface reservoir potential are from sub-tropical to arid regions. However, within carbonate build-ups some of the world’s most prolific hydrocarbon reserves are in Neogene subsurface deposits from SE Asia where the models generated in other regions cannot easily be applied. Modern and Neogene carbonate production is, and was extensive and diverse throughout the tropical waters of SE Asia.Carbonate systems in SE Asia range from mixed carbonate clastic shelves, localised and ephemeral shoals or reefs, a variety of shallow-water platform top settings and deep water and/or reworked carbonates. Despite the economic importance of Neogene carbonate systems as hydrocarbon reservoir targets there are very few studies of analogous modern or Neogene outcrops from SE Asia. This study evaluates the diagenetic alteration of two Neogene carbonate systems: clastic influenced delta-front patch reefs and an isolated platform from a semi enclosed basin. The third part of the study investigates the environmental characterisation, sedimentology and early alteration of modern fringing reef systems developed around isolated carbonate islands. Comparisons are made with other equatorial carbonate systems and subsurface reservoirs, together with those from other climate belts, thereby enhancing understanding of global carbonate development and hydrocarbon potential.Combined petrographic, geochemical and field studies reveal that mixed carbonate-siliciclastic deposits from humid equatorial coastal settings generally have low reservoir quality, due to the presence of abundant carbonatesiliciclastic matrix and the throughput of undersaturated meteoric fluids that pervasively stabilise and cement the deposits during early burial diagenesis. Also, isolated carbonate platforms that developed in protected and/or subsiding settings may possess low reservoir qualities due to abundant matrix together with extensive burial compaction, stabilisation and cementation. However, in high energy marginal settings it is likely that early marine cementation may be enhanced, with the potential to provide resistance to burial compaction effects and promote higher reservoir quality if primary porosity and pore throats are not totally occluded. The effects of meteoric dissolution in such isolated subsiding platforms is not pronounced and further mitigated by later cementation. Where reef development may have been impacted upon by potential nutrient influx there is less potential for exposure through building to sea level. Over 75% of the carbonate reservoirs in SE Asia are from isolated pure carbonate platforms. The effects of widespread vadose aragonite dissolution and large-scale reprecipitation of carbonate cements in both the vadose and particularly the phreatic marine realm lead to a layered reservoir development.A combined remote sensing and modern sedimentological study of a small-scale high energy fringing reef system reveals where grainstone textures predominate. The paucity of fines across the system as a whole is attributed to high wave/current energies, the small size of the islands rendering limited protection, bidirectional monsoon winds and the lack of reef rimmed margins built to sea level. Furthermore seagrass beds acting as baffles promote the minor accumulation of fines. It is anticipated that if early partial cementation is promoted in such grainstone deposits good quality reservoir units may be preserved. The satellite and sedimentology study probably only hints at some of the variability within SE Asia’s vast, and virtually unstudied fringing reef systems however, it highlights apparent significant differences between some equatorial fringing reefs and those from the subtropics. The systems studied here reveal the importance of seagrass bed development, the influence of the monsoons and a degree of sediment homogenisation, lack of windward-leeward effects, and a lack of hurricane influence on these equatorial SE Asian fringing reefs.